The Impact of Social Networking Sites on College Students: A Survey Study in West Bengal - Giri, Arunangshu; Biswas, Wendrila; Biswas, Debasish (Indian Journal of Marketing, 2018)
With technological progress in the past few decades, the digital era of blended technologies of communication has made efficacious improvement across the globe. Social networking sites or SNSs have had a major influence in this respect. The paper tried to analyze empirically the overriding immense impact of SNSs on the student community which has transformed their ways of learning and interacting and has bestowed a collective benefit on them. The paper delved deep into which aspects of scholastic performance of college students did the SNSs academically, socially, and behaviourally effect. Primary data were used in the study and a descriptive research design was carried out with a formalized questionnaire. A structured questionnaire with 25 items was designed to determine the factors of social networking sites that had an impact on the college students. On the basis of systematic random sampling technique, a sample of 200 students as respondents was selected from different colleges of West Bengal. Statistical analysis was executed with exploratory factor analysis and confirmatory factor analysis. Structural equation modeling was performed through AMOS-20 on the proposed conceptual model. The prime findings of the study showed that most of the factors identified brought positive development among the students. Behavioural aspects of students, as discussed in the study, did not have any impact on the comprehensive performance of the students. The study is of prominent importance as the managements of colleges can help students to augment their academic activities by providing a platform for SNSs which would also help them to socialize, associate, cooperate, and mix with the student fraternity as well as with the bigger world, thereby solidifying their overall accomplishments.